Wood extraction among the households of Zege Peninsula, northern Ethiopia - Amare, D.; Wondie, M.; Teketay, D.; Eshete, A.; Darr, Dietrich (Elsevier, 2017)
The dependence of smallholder farmers on forest resources for their sustenance and livelihoods is a major driver of deforestation and degradation of forest resources in tropical countries. Understanding the socio-economic drivers that aggravate the extraction and overexploitation of forest products is vital for designing effective forest conservation and restoration measures. This particularly holds with regard to the importance of two fundamentally opposing motivations of smallholder forest exploitation, which we label “wood extraction for need” vs. “wood extraction for greed”. This study was conducted at Zege peninsula in Northern Ethiopia to investigate the factors affecting the extraction and marketing of wood from the peninsula's primary dry Afromontane forest by smallholders. Data was collected using household survey, focus groups discussions and key informant interviews. Data analysis employed the Heckman two-steps econometric model. The predominant involvement of vulnerable households in forest exploitation suggests that wood extraction was driven by need and mainly served sustenance and safety net functions. In addition, we also found evidence of greed-driven forest exploitation. As a consequence of selective rule enforcement and nepotism, the forest enforcement committee was not effective in safeguarding the forest, there by contributing to increased wood extraction and marketing by community members for income generation. This suggests that, in order to protect the forest, interventions are needed that aim at creating alternative income opportunities for smallholders through improved production of non-timber forest products, enhanced market access and the provision of locally adapted technologies; as well as at increasing the integrity of law enforcement.